Relativistic kinetics and hydrodynamics of hot collisional plasmas - Marushchenko, I.; Azarenkov, N.A. (Problems of Atomic Science and Technology, 2022)
In the paper, relativistic equations of local hydrodynamics for the laboratory fusion plasmas are obtained. Relativistic effects in the physics of electron transport appear primarily because of macroscopic features of relativistic thermodynamic equilibrium given by the Maxwell-Jüttner distribution function, and the characteristic velocity of plasma flow is significantly small: V << νₜₑ < c. We propose an approach in which the plasma electrons are treated as fully relativistic and the hydrodynamic flow is treated in the weakly relativistic approximation. For convenience, the obtained relativistic effects are divided between “quasi-relativistic” terms, which in the nonrelativistic limit coincide with well-known expressions, and fully relativistic terms, which disappear at c → ∞. The considered mixed approach can be useful for construction of transport models for numerical studies of both astrophysical objects and hot fusion plasma.